Biopolitics, thanatopolitics and the right to life - Nasir, Muhammad Ali (Theory, culture & society, 2017)
This article focuses on the interrelationship of law and life in human rights. It does this in order to theorize the normative status of contemporary biopower. To do this, the case law of Article 2 on the right to life of the European Convention on Human Rights is analysed. It argues that the juridical interpretation and application of the right to life produces a differentiated governmental management of life. It is established that: 1) Article 2 orients governmental techniques to lives in order to ensure that both deprivation and protection of lives is lawful; 2) A proper application of Article 2 grounds itself on a proper discrimination of lives which causes Article 2 to be applied universally but not uniformly to all juridical subjects; 3) The jurisprudence of Article 2 is theoretically appreciable only in a 'politics of life'. Finally, the article ends with a plea to analyse other fundamental human rights in the context of 'biopolitical governmentality'.